USING SOCIAL NETWORK ANALYSIS TO EVALUATE COMMUNITY CAPACITY BUILDING OF A REGIONAL COMMUNITY CANCER NETWORK - Luque, John (2010)
The Tampa Bay Community Cancer Network (TBCCN) is one of 25 Community Network Programs funded by the National Cancer Institute’s (NCI’s) Center to Reduce Cancer Health Disparities with the objectives to create a collaborative infrastructure of academic and community based organizations and to develop effective and sustainable interventions to reduce cancer health disparities. In order to describe the network characteristics of the TBCCN as part of our ongoing evaluation efforts, we conducted social network analysis surveys with our community partners in 2007 and 2008. One key finding showed that the mean trust value for the 20 community partners in the study increased from 1.8 to 2.1 (p<0.01), suggesting a trend toward increased trust in the network. These preliminary results suggest that TBCCN has led to greater collaboration among the community partners that were formed through its capacity-building and evidence-based dissemination activities for impacting cancer health disparities at the community level.